Smart home low-carbon environment protection realization method - CHEN SI; LI WEI (2016)
The invention discloses a smart home low carbon environment protection realization method, which comprises the following steps: initializing a protocol, scanning channels, establishing a ZigBee network, monitoring network information, carrying out node-having network access application, allocating addresses, information request, information type, terminal data information collecting, uploading data to a user, user sending, information control, transmitting data to a terminal node, algorithm adaptive learning and low-carbon environment protection algorithm. Smart home low-carbon environment protection is realized through automatic learning perception algorithm+ZigBee, true "smart" is realized, and equipment can learn and sense living habits, life style and demands in different ages of people; through the "smart" technology and algorithm, the equipment is allowed to learn and sense life styles of people, and then, turn off or darken some equipment according to use time and conditions; and big data statistics is